1997
DOI: 10.1038/sj.onc.1201593
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-10b directs hypermorphic development and transformation in mammary glands of male and female mice

Abstract: Wnt-10b is expressed during the formation of the mammary rudiment in mouse embryos and its expression continues through puberty when the mammary ductal pattern is established under control of ovarian steroids. Recently, viral activation of the Wnt-10b locus has linked its overexpression to mammary tumor formation, suggesting a role for Wnt-10b in patterning and growth-regulation of the mammary gland. To test this notion, we created lines of transgenic mice that express elevated levels of Wnt-10b under the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
107
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(115 citation statements)
references
References 18 publications
7
107
0
1
Order By: Relevance
“…Consistent with this idea, transgenic mice that express elevated Wnt10b from the mouse mammary tumor virus promoter show developmental alterations in the mammary gland, including expanded glandular development and precocious appearance of alveoli in virgin females (38). Expression of Wnt10b from the FABP4 promoter results in a different phenotype, with greatly impaired development of mammary glands (data not shown).…”
Section: Discussionsupporting
confidence: 60%
“…Consistent with this idea, transgenic mice that express elevated Wnt10b from the mouse mammary tumor virus promoter show developmental alterations in the mammary gland, including expanded glandular development and precocious appearance of alveoli in virgin females (38). Expression of Wnt10b from the FABP4 promoter results in a different phenotype, with greatly impaired development of mammary glands (data not shown).…”
Section: Discussionsupporting
confidence: 60%
“…Thus, Lef1 and Wnt10b are the likely transcription factor and ligand, respectively, mediating Wnt/␤-catenin signaling during fungiform papillae formation. Although Wnt10b has not been well characterized biochemically, there are several examples demonstrating Wnt10b's function as a ligand for the Wnt/␤-catenin signaling pathway (27)(28)(29)(30). In addition, we have confirmed that Wnt10b induces double axis formation when expressed in Xenopus embryos (K.I.…”
Section: Discussionsupporting
confidence: 57%
“…Generation of Transgenic Mice-The human COX-2 gene (23) was cloned behind the murine mammary tumor virus (MMTV) promoter (24). The linearized construct was used to derive transgenic CD1 mice (Charles River Laboratories) in the UCHC transgenic core facility.…”
Section: Methodsmentioning
confidence: 99%
“…Whole Mount, Histological Methods, and ImmunohistochemistryMammary glands were dissected and processed for whole mount analysis as described (24,26). Some glands were fixed and analyzed by histological methods (28).…”
Section: Methodsmentioning
confidence: 99%